THE ROLE OF ATTRACTIVENESS OF ALTERNATIVES IN GEN-AI PLATFORM SWITCHING INTENTION AMONG INDONESIAN UNIVERSITY STUDENTS - Satrio Tegar Sadewo; Aditya Kumala Dewi; Sofyan Ashari Nur; Nisa' Ulzahro; Dimas Ihsan Pratama (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This study examines the role of Attractiveness of Alternatives (AoA) in driving Gen-AI platform switching intention among Indonesian university students. TAM is widely used to explain technology adoption but lacks the ability to account for competitive pull factors in multi-platform environments. Integrating TAM with Push-Pull-Mooring (PPM) theory, this study tests the effects of Perceived Usefulness (PUS), Perceived Ease of Use (PEU), and AoA on switching intention, along with the moderating role of AoA. Research Methodology: Data were collected from 444 Indonesian university students who had experience using Gen-AI platforms (e.g., ChatGPT, Gemini, Copilot) through an online questionnaire with purposive sampling. The structural model was analyzed using PLS-SEM with SmartPLS 4. Results: PUS and PEU did not significantly predict switching intention, while AoA had a strong positive effect (β = 0.475, p < 0.001, f² = 0.272). The moderating effects of AoA were not supported. Conclusions: In low-switching-cost digital environments, the attractiveness of alternative platforms is the dominant driver of switching intention, while current platform evaluations lose their explanatory power. Limitations: The cross-sectional design and reliance on a student sample limit causal inference and generalizability to other user populations. Contributions: This study identifies boundary conditions under which TAM constructs lose predictive power for switching behavior and empirically validates AoA as the dominant pull factor in Gen-AI platform contexts, supporting the integration of PPM mechanisms into TAM-based switching research. The findings also offer practical insights for Gen-AI providers, emphasizing that competitive positioning matters more than incremental usability improvements.